(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2025)
This article analyzes the effect of various defects on yarn. in yarn and man-made yarns, thicker threads are formed as a result of the strip being torn off. This defect is caused by the fact that the tape is not connected correctly. As a result of research, measures to prevent tape rupture were analyzed.